Substitusi tepung kacang merah meningkatkan kandungan gizi, serat pangan, dan kapasitas antioksidan beras analog sorgum - Fauziyah, A'immatul; Marliyati, Sri Anna; Kustiyah, Lilik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The objectives of this research were to determine the formula of sorgum artificial rice (SAR), analyze nutrient and fiber content, and antioxidant capacity of SAR each formula and find the best formula of SAR. The artificial rice was made of sorgum flour (substituted by red kidney bean flour (RKF) for 5% (F1), 10% (F2), and 15% (F3)), water, porang flour, GMS (gliserine monostearate), and soy protein isolate. Nutrient content and antioxidant capacity were analyzed using AOAC and spectrophotometry method. Based on the rank of nutrient, fiber content, and antioxidant capacity, the best formula was F3 which its moisture, ash, protein, fat, carbohydrate, and energy content were 6.75%, 1.37%, 15.50%, 1.19%, 75.19%, and 373.52 kcal/100 g, respectively. Soluble and insoluble fiber content of F3 each was 4.88% and 7.26%. Antioxidant capacity of F3 were 113.93 mg vitamin C/100 g. Substitution level of RKF on SAR significantly (p<0.05) increased content of ash, protein, fat, carbohydrate, energy, fiber, and antioxidant capacity of the SAR.